2020
DOI: 10.3390/educsci10110298
|View full text |Cite
|
Sign up to set email alerts
|

“Let’s Talk about It”—Explicit Discussions as a Way to Reduce the Resistance of Religious Jewish Science Teachers to Learning and Teaching about Evolution: A Case Study

Abstract: Acknowledging the diverse perceptions about science–religion relationships among learners who come from various religious environments may increase learners’ willingness to learn about evolution. This study is based on a zoology course designed for in-service teachers, which aimed to provide basic scientific knowledge about evolution using the Religious Cultural Competence in Evolution Education framework. The study explores whether learners who were resistant to evolution modify their attitudes and willingnes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A recent study that was conducted among in-service teachers in Israel, Stahi-Hitin and Yarden Evolution: Education and Outreach (2022) 15:18 indicated that using the ReCCEE framework increased some formerly "resistant" learners' willingness to learn about evolution and include it in their own teaching. In addition, using the ReCCEE practices created a liberal and relaxing atmosphere that enabled the teaching of evolution-even human evolution-within a group of culturally diverse and antagonistic participants (Alkaher et al 2020).…”
Section: Relating To Religion In a Science Classmentioning
confidence: 99%
“…A recent study that was conducted among in-service teachers in Israel, Stahi-Hitin and Yarden Evolution: Education and Outreach (2022) 15:18 indicated that using the ReCCEE framework increased some formerly "resistant" learners' willingness to learn about evolution and include it in their own teaching. In addition, using the ReCCEE practices created a liberal and relaxing atmosphere that enabled the teaching of evolution-even human evolution-within a group of culturally diverse and antagonistic participants (Alkaher et al 2020).…”
Section: Relating To Religion In a Science Classmentioning
confidence: 99%